Number 36 (March 1998) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1998)
(March 1998) - Distribution and habitat affinities of the blackmouth shiner (Notropis melanostomus) in Mississippi, including eight newly discovered localities in the Upper Pascagoula River Drainage. By Martin T. O'Connell, Stephen T. Ross, John A. Ewing III and William T. Slack The bluebarred pygmy sunfish (Elassoma okatie) in Georgia. By Jan Jeffrey Hoover, Steven G. George and Neil H. Douglas Minutes, Business Meeting, 23rd Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: blackmouth shiner; notropis melanostomus; fishes; upper pascagoula river; bluebarred pygmy sunfish; elassoma okatie